Pregnancy outcomes and anxiety in nulliparous women. (12th December 2022) - Gimbel, Lauren A.; Blue, Nathan R.; Allshouse, Amanda A.; Silver, Robert M.; Gimbel, Bruce; Grobman, William A.; Haas, David M.; Simhan, Hyagriv N.; Mercer, Brian M.; Hatfield, Tamera
Abstract: Objective: To examine pregnancy outcomes in women with treated and untreated anxiety in a well-characterized cohort. Study Design: Secondary analysis of the NuMoM2b study, a prospective multi-center cohort of nulliparous women. Anxiety was assessed at 6 weeks 0 days − 13 weeks 6 days using the State Trait Anxiety Inventory (STAI-T). Women were divided into three groups: anxiety and medical treatment, anxiety and no medical treatment, and no anxiety (controls). The primary outcome was a composite of preterm birth, small for gestational age infant, placental abruption (clinically diagnosed), and hypertensive disorders of pregnancy. Multivariable logistic regression was used to adjust for potential confounding variables. Results: Among 8293 eligible women, 24% ( n = 1983) had anxiety; 311 were treated medically. The composite outcome (preterm birth, small for gestational age infant, placental abruption, hypertensive disorders of pregnancy) occurred more often in women with untreated anxiety than controls (28.6% vs 25.9%, p =.02), with no difference between treated anxiety and controls (27.7% vs 25.9%, p =.49). After adjustment for confounders, including controlling for depression, there were no differences in the primary outcome among groups. Untreated anxiety remained associated with increased odds of neonatal intensive care unit admission. Conclusion: Anxiety occurred in almost a quarter of nulliparas. There was no association between treated or untreated anxiety and our primary outcome of adverse pregnancy outcomes after adjustment for confounders. However, neonates born to women with untreated anxiety were at increased risk for NICU admission.